Evaluation of the dynamic response of ISA-Hypoplastic model in problems with repetitive loading (2023)
Accurate numerical predictions of the behavior of soil deposits subjected to liquefaction are essential to guarantee the safety of civil infrastructure. Furthermore, many geotechnical structures experience cyclic loading throughout their design life, such as offshore structures, pavements, water tanks, among others. It is evident that robust constitutive models are necessary to accurately reproduce the mechanical behavior of soils in these cases. However, there is still a considerable degree of uncertainty in the available continuum mechanics-based numerical methodologies and constitutive models that are currently being used. Therefore, research works that identify their drawbacks, performance, and extend the capabilities of these models is of high importance to the geotechnical community. This thesis focused on extending and evaluating an advanced hypoplastic model for sands with Intergranular Strain Anisotropy (ISA). Initially, the previous version of the hypoplastic model with ISA was extended by incorporating cyclic mobility effects through a second-order fabric-dilatancy tensor. The extended model showed much improved capabilities in predicting liquefaction. Subsequently, the extended model was applied to simulate an offshore wind turbine monopile with typical wind and wave characteristics of the Caribbean coast of Colombia. Next, a series of dynamic centrifuge tests representing a liquefiable sloping ground from the Liquefaction Experiment and Analysis Projects (LEAP) 2017 were simulated using the extended model. Finally, the extended model was further enhanced to incorporate the influence of highly plastic fines on liquefaction resistance.